2019
DOI: 10.7555/jbr.31.20170038
|View full text |Cite
|
Sign up to set email alerts
|

Association between exposure to particulate matter during pregnancy and birthweight: a systematic review and a metaanalysis of birth cohort studies

Abstract: Studies of the associations between maternal exposure to particulate matter (PM) and risk of adverse effects on fetal growth are inconsistent and inconclusive. This question can be well answered by carefully designed birth cohort studies; however, so far the evidence from such studies has not come to the same conclusion. We sought to evaluate the association between maternal exposures to PM and low birthweight (LBW) enrolling 14 studies from 11 centers, and to explore the influence of trimester and exposure as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The current study showed a positive but statistically non-significant association between prenatal PM 10 exposure and ABOs, which is consistent with the existing evidence on non-significant association [ 72 , 74 ]. Despite the inconsistent results shown by earlier reviews [ 72 , 74 , 75 ], according to the recent review [ 26 ], a number of studies conducted in the ICS have shown a significant association between PM 10 and PTB [ 18 , 27 , 29 , 35 ] and LBW [ 27 , 29 , 32 , 33 , 53 ]. One of the reasons for the currently established non-significant association with PM 10 could be that the average annual concentration is on the borderline of the recommended air quality guideline by WHO [ 71 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study showed a positive but statistically non-significant association between prenatal PM 10 exposure and ABOs, which is consistent with the existing evidence on non-significant association [ 72 , 74 ]. Despite the inconsistent results shown by earlier reviews [ 72 , 74 , 75 ], according to the recent review [ 26 ], a number of studies conducted in the ICS have shown a significant association between PM 10 and PTB [ 18 , 27 , 29 , 35 ] and LBW [ 27 , 29 , 32 , 33 , 53 ]. One of the reasons for the currently established non-significant association with PM 10 could be that the average annual concentration is on the borderline of the recommended air quality guideline by WHO [ 71 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, the systematic review by Sapkota et al [ 72 ] found that PM 2.5 exposure during the first trimester increased the PTB risks, while the LBW results were inconclusive. On the other hand, the comprehensive review by Klepac et al [ 73 ] reported heterogeneity with both first and third-trimester exposure and PTB, whereas the review and meta-analysis by Ji et al [ 74 ] showed a higher publication bias on the association between LBW and third-trimester PM 2.5 exposure. Thus, studies seem to have a heterogenous association with ABOs on the trimester-specific PM 2.5 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Three prior meta-analyses [12,13,24] found the higher PM 2.5 was associated with higher risk of LBW or TLBW. Our results for TLBW are generally consistent with these reviews.…”
Section: Discussionmentioning
confidence: 99%